Going green: Purchase intention of DLSU 119 students towards social enterprises - Panuelos, Liam Dominic A. (Animo Repository, 2023)
Over the past few years, there has been a growth in the urgency to support sustainability missions. This has been particularly evident in the realm of business and commerce. There has been an increasing number of people who would rather purchase from sustainable brands than non-sustainable brands, especially among today’s youth. The discussion surrounding sustainability has specifically exploded in the Philippines as one of the primary countries affected by climate change. This phenomenon has piqued the interest of the researchers in investigating the Purchase Intention of ID 119 students in De La Salle University-Manila (DLSU-M) towards social enterprises in the Philippines. Students of DLSU-M were chosen as the main target of this research due to their proximity to the researchers. The Independent Variables that were measured in the study are Sustainability Efforts and Perceived Value, while the Dependent Variable is Purchase Intention. Additionally, these variables are moderated by Sustainability Orientation. A mixed-method study was utilized in this research, with 362 ID 119 students answering an online questionnaire and an additional three small social enterprises in the Philippines were interviewed virtually to provide supplementary information and substantiate the obtained data from the students. The group used the brand TOMS as a benchmark to compare the data from said small businesses as TOMS is a popular choice among DLSU-M students. Subsequent findings of the conducted regression analyses revealed that Sustainability Efforts and Perceived Value have a significant impact on Purchase Intention, while Sustainability Orientation did not serve as a moderator towards the relationship between Independent and Dependent Variables. The conducted pattern matching also affirms that the interviewed businesses share the same sentiments with the surveyed students when it comes to sustainability. With this, the researchers have recommended were focused on enhancing TOMS’ Sustainability Efforts and Perceived Value. Moreover, specific recommendations were also proposed such as expanding TOMS sustainable product line and implementing a new marketing campaign. Further research may look into the time that consumers take in deciding whether they should purchase a sustainable good or not and how it affects the frequency of their purchase. It is also recommended that future research look into other sustainable companies other than TOMS and conduct research on a different demographic. The sustainable businesses industry may take advantage of this study by becoming more transparent about their CSR activities and adopt a user-generated content marketing strategy to boost sales. Lastly, the researchers recommended that consumers continue to buy more sustainably as there was a high number of responses that mentioned their reluctance to commit to sustainable clothing. Keywords: Sustainability Efforts, Perceived Values, Purchase Intention, Sustainability Orientation, TOMS, ID 119, DLSU-M, Social Enterprise